Revolutions in Sovereignty : How Ideas Shaped Modern International Relations. - Philpott, Daniel (Princeton University Press, 2008)
How did the world come to be organized into sovereign states? Daniel Philpott argues that two historical revolutions in ideas are responsible. First, the Protestant Reformation ended medieval Christendom and brought a system of sovereign states in Europe, culminating at the Peace of Westphalia in 1648. Second, ideas of equality and colonial nationalism brought a sweeping end to colonial empires around 1960, spreading the sovereign states system to the rest of the globe. In both cases, revolutions in ideas about legitimate political authority profoundly altered the "constitution" that establish.